2023
DOI: 10.3390/nu15030506
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Semi-Quantitative Food Frequency Questionnaire to Estimate Macronutrient Intake among Type 2 Diabetes Mellitus Patients in Malaysia

Abstract: The Food Frequency Questionnaire (FFQ) is one of the most frequently used instruments in epidemiological studies for evaluating dietary intake. Because of the variety of dietary habits within different populations, an FFQ must be tailored to the specific group. To date, no specific FFQ has been developed for type 2 diabetes mellitus (T2DM) patients in Malaysia. In this study, we developed a semi-quantitative FFQ to estimate macronutrient intake among T2DM patients. The development of the FFQ was based on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Doxercalciferol, a vitamin D receptor agonist, highlights the close association between vitamin D deficiency and conditions such as diabetes, arterial hypertension, and chronic kidney disease (34,35). The detection of nuclear vitamin D receptors (VDRs) in vascular endothelial cells and cardiomyocytes indicates that vitamin D is directly involved in the development and progression of cardiovascular diseases (36,37). Topiramate, promotes insulin secretion and enhances insulin sensitivity, offering an effective solution for the critical challenges of b-cell dysfunction and insulin resistance in T2DM (38).…”
Section: Discussionmentioning
confidence: 99%
“…Doxercalciferol, a vitamin D receptor agonist, highlights the close association between vitamin D deficiency and conditions such as diabetes, arterial hypertension, and chronic kidney disease (34,35). The detection of nuclear vitamin D receptors (VDRs) in vascular endothelial cells and cardiomyocytes indicates that vitamin D is directly involved in the development and progression of cardiovascular diseases (36,37). Topiramate, promotes insulin secretion and enhances insulin sensitivity, offering an effective solution for the critical challenges of b-cell dysfunction and insulin resistance in T2DM (38).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia could be both a cause and effect of COVID 19 infection. Lower vitamin D levels have also been a shown to predispose to the development of insulin resistance and type 2 diabetes [34] . Thus, the ill effects of low vitamin D levels could also act via its effect on hyperglycaemia.…”
Section: Common Associations Of Low Vitamin D That Also Predispose To...mentioning
confidence: 99%
“…11 Recently, emerging evidence has revealed that reasonable dietary patterns, especially for appropriate proportions of macronutrients, contribute to the improvement of metabolic diseases. 12,13 However, how the dietary pattern of macronutrients determines the pathological progress of ALD is largely unknown.…”
Section: Introductionmentioning
confidence: 99%